0278 Changes in Sleep Architecture During Long-Duration Spaceflight. (27th May 2020) - Piltch, O; Flynn-Evans, E; Stickgold, R
Abstract: Introduction: Previous projects have shown that astronauts sleep significantly worse in mission than on Earth. However, it is unclear how sleep architecture is influenced by microgravity. Such information could inform our understanding of the adaptive mechanisms NREM and REM sleep on Earth. We investigated how sleep architecture is affected during spaceflight relative to on Earth. Methods: Sleep architecture was assessed using the Nightcap monitor before (pre-flight, n=113 nights), during (in-flight, n=68 night), and after (post-flight, n=61 nights) missions aboard the Mir space station for four cosmonauts and one astronaut. We compared hand-scored REM/NREM/wake staging in/post-flight to a pre-flight baseline using mixed-effects regression to account for subject variability. We also used mixed-effects modeling to assess changes over time in different phases of the mission. Results: Participants averaged an hour less sleep in space (5.4 ± 0.66) compared to pre-flight (6.6 ± 0.70; p < .0001) and spent significantly more time awake in bed, leading to a 20.8% reduction in sleep efficiency. Sleep architecture was also affected by spaceflight: percentages of time in bed for NREM and REM decreased significantly by 9.9% and 26.6% respectively. REM latency nearly doubled during spaceflight to 88 ± 3 minutes. All metrics were stable across the in-flight phase, with the exception of an increase in sleep latency (β: 0.47; p = 0.0009) and a decrease in time in bed (β = 0.85; p < .0001). Conclusion: These data substantiate previous findings focused on sleep continuity in microgravity. A variety of metrics demonstrate worse sleep in space. NREM and REM time significantly decreased alongside an increase in wakefulness, but the relative proportion of these stages also changed significantly: REM sleep suffered more than NREM in spaceflight conditions. These longitudinal data add value to our nebulous understanding of how sleep functions in microgravity. Support: Mary Gordon Roberts Fellowship, NAS 9-19406, NIMH #MH-48, 832, The MacArthur Foundation Mind-Body Network, and Healthdyne Technologies